Perancangan Sistem Buku Tamu Digital dalam Museum Musik Indonesia - Salim, M. Alfi Nuris; Sana, Salma; Aulia, Nafisha Ilmi; Prasetya, Aliya Afifah; Utami, Rachma Bhakti (Transpublika Publisher, 2025)
The Indonesian Music Museum (MMI) is an institution that preserves the history of Indonesian music that in its operational process requires an efficient and informative guest visit recording system. The implementation of a manual guest book recording system has several weaknesses and shortcomings that can cause losses to the Indonesian Music Museum. The purpose of this research is to design and implement a digital-based guest book using the PHP RAD framework at the Indonesian Music Museum as a form of optimizing the development of the latest technology. This research uses the Action Research method. The data collection technique in this study was through observation and interviews, followed by needs analysis, system design, implementation, system testing, application and maintenance of the system. The results of the study showed that the use of this digital system was able to increase the accuracy of visitor data, speed up the recording process, and facilitate the analysis of visitor data in real time. The digital-based guest book recording system also allows the Indonesian Music Museum to collect visitor demographic data that is useful for developing programs and data-driven decision-making.